Jehovah’s Witnesses’ Adoption of Digitally-Mediated Services During Covid-19 Pandemic - Torres-Pruñonosa, Jose; Plaza-Navas, Miquel Angel; Brown, Silas S. (Taylor & Francis, 2022)
This is the first paper to analyse the digitalisation measures that Jehovah’s Witnesses adopted during the pandemic and their behavioural consequences. The paper examines how the Witness community met the challenges of the pandemic by rapidly shifting to prerecorded and videoconference meetings, allowing online interaction between congregants. Based on a survey and focus groups, the effect of digitalisation of meetings on the feelings and attitudes to learning of Witnesses is analysed, investigating to what extent digitally-mediated religious services affected them in comparison with in-person meetings with regard to prayers, songs, speaking assignments, audience comments and social interaction, in both active and passive roles. The main conclusions are that digital meetings did not diminish their feelings of relationship with God or their intellectual learning, but performed less well than in-person meetings with regard to songs and social interaction. The authors reflect on how Jehovah’s Witnesses, while strictly upholding COVID-19 measures (they did not meet physically even where legally allowed due to their respect for life), navigated their feelings in the transcendent experience of uniting believers in a virtual environment.
La Adopción de Servicios Religiosos Digitales en los Testigos de Jehová Durante la Pandemia del COVID-19
Este es el primer artículo que analiza las medidas de digitalización que adoptaron los testigos de Jehová durante la pandemia y las consecuencias en su comportamiento. El artículo examina cómo afrontó esta comunidad religiosa los retos de la pandemia cambiando rápidamente a reuniones pregrabadas y por videoconferencia, lo que permitió la interacción online entre los congregantes. A partir de una encuesta y de varios grupos focales, se analiza el efecto de la digitalización de las reuniones en los sentimientos y las actitudes relacionadas con el aprendizaje de los testigos, investigando hasta qué punto los servicios religiosos realizados a través de medios digitales les afectaron en comparación con las reuniones presenciales en lo que respecta a las oraciones, las canciones, las asignaciones de oratoria, los comentarios del público y la interacción social, tanto en lo referente a roles activos como pasivos. Las principales conclusiones son que las reuniones digitales no disminuyeron sus sentimientos relativos a su relación con Dios ni su aprendizaje intelectual, pero tuvieron un rendimiento inferior al de las reuniones presenciales en lo que respecta a las canciones y la interacción social. Los autores reflexionan sobre cómo los testigos de Jehová, a pesar de mantener estrictamente las medidas relativas al COVID- 19 (no se reunían físicamente ni siquiera cuando lo permitía la ley debido a su respeto por la vida), gestionaban sus sentimientos en la experiencia trascendente de unir a los creyentes en un entorno virtual.
Keywords: digitalization; Jehovah’s witnesses; meetings; feelings; COVID-19; religion; social interaction; digitalización; testigos de Jehová; reuniones; sentimientos; COVID- 19; religión; interacción social; Scopus; Emerging; Scopus